Penanaman Karakter Penalaran Matematis Dalam Pembelajaran Matematika Melalui 1 Pola Pikir Induktif-Deduktif - Mulin Nu’man (Jurnal Fourier, 2012)
One of the mathematics learning purposes is using reasoning in patterns and properties, mathematical manipulation in making generalization, compiling evidence, or explaining mathematical ideas and statements. Mathematical learning based on behaviorism has been seen as less successful in instilling character of mathematics reasoning. Therefore, it is necessary to find alternative learning not only teaching but instilling character of mathematical reasoning. This paper offers constructivist in mathematics learning, which is one of the ways to involve the use of inductive-deductive thinking. Activities that involve students learning to use the inductive-deductive mindset needs to be designed and implemented by teachers. Using inductive thinking can be conditioned, especially in the process of understanding a concept or generalization. Deductive thought patterns can be conditioned to improve mathematical reasoning, for example, in the proofing. The mindset of inductive and deductive mathematical reasoning is difficult to separate in the mathematical reasoning therefore it is regarded involving the use of inductive-deductive thinking.